Touring Girls - Atanga, George Che, 1956- (Book collections on Project MUSE., 2014)
Touring Girls tells the story of Jacob Mbuy a young Cameroonian whose primary objective in life is having affairs with as many women as possible. He is obsessed with abusing young girls as well as instilling hopeless hope in adult women. His demise comes when he changes his world from the Christian to the Moslem world where he confronts a new type of women who behave strangely and cannot dance to his tunes. Protected by Islamic traditions and strict government laws, Jacob lands into a hell of unprecedented problems.